Effects of hypohydration and menstrual phase on pain : a thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, School of Sport, Exercise and Nutrition, Massey University, Palmerston North, New Zealand - Tan, Beverly Wei Lin (Massey University, 2021)
Chronic pain is a pervasive health problem and is associated with tremendous societal and economic costs. However, current pain treatments are often ineffective because there are multiple factors that contribute to a person’s experience of pain. Recent research showed that mild hypohydration increases experimental pain sensitivity in men, but whether this also occurs in women has not been examined. The fluctuations in ovarian hormone (i.e., 17ß-oestradiol and progesterone) concentrations throughout the menstrual cycle may influence a woman’s pain sensitivity, as well as hydration levels. Therefore, interactions between hypohydration and the menstrual phase on pain may exist. To test this hypothesis, this thesis investigated the effects of hypohydration (induced by 24 hr of fluid restriction) on ischaemic pain sensitivity in 14 healthy, eumenorrheic women during the early follicular and mid-luteal phases of their menstrual cycle. In addition, the potential efficacy of acute water ingestion as a countermeasure to the negative impact of hypohydration on pain was also examined. Blood and urinary markers of hydration status indicated that 24 hr of fluid restriction successfully induced mild hypohydration. The major finding is that mild hypohydration reduced ischaemic pain tolerance (by 34 ± 46 s; P = .02, ηp 2 = .37) and increased subjective ratings of both pain intensity (by 0.7 ± 0.7 cm; P = .004; ηp 2 = .55) and pain unpleasantness (0.7 ± 0.9 cm; P = .02; ηp 2 = .40), irrespective of menstrual phase. Menstrual phase had no apparent effect on pain sensitivity or on hydration status. Acute water ingestion decreased thirst sensation (by 2.3 ± 0.9 cm; P < .001, ηp 2 = .88) but did not reverse the hyperalgesic effects of hypohydration. The effects of hypohydration on pain sensitivity were not explained by differences in state anxiety levels or mood state. In conclusion, the findings from this thesis extend to women, previous data in men that showed increases in pain sensitivity with mild hypohydration. This thesis also provides strong evidence that the menstrual phase does not influence pain sensitivity, after hydration status was controlled, the influence of potential confounders was minimised, and when menstrual phases were accurately verified. Lastly, these findings underscore the importance of ingesting fluids regularly throughout the day to maintain adequate hydration and avoid dehydration, especially for individuals experiencing pain.
Keywords: Pain; Dehydration (Physiology); Menstrual cycle; 420702 Exercise physiology